Possibly imperfect ontologies for effective information retrieval - Nagypál, Gábor (KIT Scientific Publishing, 2007)
Ontologies and semantic metadata can theoretically solve all problems of traditional full-text search engines. In practice, however, they are always imperfect. This work analyzed whether the negative effect of ontology imperfection is higher than the positive effect of exploiting the ontology features for IR. To answer this question, a complete ontology-based information retrieval system was implemented and thoroughly evaluated.